Autonomic neuropathy in rheumatoid arthritis. Issue 6183 (21st July 1979) - Edmonds, M E; Jones, T C; Saunders, W A; Sturrock, R D
Abstract : Patients with seropositive and seronegative rheumatoid arthritis (RA) and age-matched controls were investigated for the presence of autonomic neuropathy. Significantly more patients with RA had abnormal autonomic function, suggesting that autonomic neuropathy occurs more commonly in RA than hitherto suspected. The existence of an autonomic neuropathy may be an important complicating factor in rheumatoid disease and may lead to increased morbidity and mortality.